Η διαχείριση των νοσηλευτικών λαθών με τη χρήση εργαλείων ποιότητας - Λουκά, Άντρη (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2011)
Introduction: Undoubtedly, errors in clinical practice are defined as any unintentional incident which poses a threat to patient safety or as any deviation from the rules and established practices of the workplace. These errors are, unfortunately, a daily occurrence in health care provision, and have a direct impact on the therapeutic efficacy and safety of the patient. Over the years the number of errors is growing and affects the quality of health care services and consequently undermining the credibility of nursing. Nevertheless, research and methodological approaches are being utilized to ensure ongoing quality services. This paper refers to specific tools that have been developed. Purpose: This study pinpoints the management of medical errors through the use of the above tools. Additionally, it analyzes the factors that lead to nursing mistakes, their management at the individual and collective level, and the role of health professionals in the prevention and prompt recognition of such errors. Material and method: Literature databases (PUBMEND, CINAHL, IATROTEK, SCOPUS) were used for the literature review. In addition through the use of ESF and by using the command ‘The management of medical errors by using quality tools’ we found fourteen articles, thirteen of which met the entry criteria, one Doctorate thesis and one Master’s thesis. Books and manuals were also used. Entry Criteria: Keywords, in Greek and in English, analyzing the related concepts. Results: The complexity of clinical care and of human behavior prevents the complete elimination of risk. Nurses are called to create a safety culture that will minimize the risk of adverse incidents through the utililization of quality tools that have an obvious value. Conclusions:The health sector is required to use risk management tools, which are already available, and to develop their own plans for the management of clinical risk.
Keywords: Medical Errors--prevention & control; Patient safety; Attitude